Pendidikan Calon Guru Paud Berbasis Pendekatan Holistik-Integratif - Satriani (Jurnal Ilmu Pendidikan Guru Sekolah Dasar dan Usia Dini, 2025)
This study aims to explore the implementation of the holistic-integrative approach in the education of prospective Early Childhood Education (ECE) teachers. The holistic-integrative approach is considered a comprehensive strategy that combines various aspects of child development—including physical, cognitive, social, emotional, and spiritual domains—while also promoting collaboration between schools, families, and social services. The research employs a qualitative descriptive approach, utilizing in-depth interviews, participatory observation, and document analysis in several ECE teacher education programs. Findings indicate that although prospective teachers have begun to understand the concept, its application remains largely theoretical and has not been fully integrated into the curriculum or learning practices. Key challenges include limited cross-sector involvement, weak curriculum integration, and insufficient practical field experiences. Therefore, curriculum reformulation, lecturer capacity-building, and strategic partnerships with ECE institutions implementing the holistic approach are necessary. A teacher education model based on this approach is believed to foster competent and responsive educators capable of supporting children’s development in a comprehensive and inclusive manner.